Development, Quantification, Method Validation, and Stability Study of a Novel Fucoxanthin-Fortified Milk - Mok, Il-Kyoon; Yoon, Jung-Ro; Pan, Cheol-Ho; Kim, Sang Min (AMER CHEMICAL SOC, 2016)
To extend the scope of application of fucoxanthin, a marine carotenoid, whole milk (WM) and skimmed milk (SM) were fortified with fucoxanthin isolated from the microalga Phaeodactylum tricornutum to a final 8 mu g/mL milk solution concentration. Using these liquid systems, a fucoxanthin analysis method implementing extraction and HPLC-DAD was developed and validated by accuracy, precision, system suitability, and robustness tests. The current method demonstrated good linearity over the range of 0.125-100 mu g/mL fucoxanthin with R-2 = 1.0000, and all validation data supported its adequacy for use in fucoxanthin analysis from milk solution. To investigate fucoxanthin stability during milk production and distribution, fucoxanthin content was examined during storage, pasteurization, and drying processes under various conditions. Fucoxanthin in milk solutions showed better stabilizing effect in 1 month of storage period. Degradation rate constant (k) on fucoxanthin during this storage period suggested that fucoxanthin stability might be negatively correlated with decrease of temperature and increase of protein content such as casein and whey protein in milk matrix. In a comparison between SM and WM, fucoxantin in SM always showed better stability than that in WM during storage and three kinds of drying processes. This effect was also deduced to relate with protein content. In the pasteurization step, >91% of fucoxanthin was retained after three pasteurization processes even though the above trend was not found. This study demonstrated for the first time that milk products can be used as a basic food matrix for fucoxanthin application and that protein content in milk is an important factor for fucoxanthin stability.
Keywords: HPLC-UV METHOD; BETA-CAROTENE; EXTRACTION; EMULSIONS; LYCOPENE; OILS